2016
DOI: 10.1515/jlst-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing passengers’ choice of transport mode to Warsaw Chopin Airport

Abstract: Airport accessibility is an important factor for airport choice and therefore also for airport competition. When air passengers choose an itinerary, they reflect on the transport chain from door to door. Therefore, factors affecting the traveller’s decision for a particular option go beyond the price and quality of air services from airport to airport. The decision for or against a particular air service and a particular airport is to a certain extent dependent on the accessibility of the airport. The aim of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(9 reference statements)
0
0
0
Order By: Relevance
“…Passengers choose rail and bus in accordance with distance, price/value for money, time, and accessibility as key factors (Gatwick Airport, 2016). Gorecka (2016) confirmed that cost and time are major factors. Gatwick Airport (2016) only provides an overview of results so it is not clear as to the representativeness of the data.…”
Section: : Factors Affecting Airport Modal Choicementioning
confidence: 74%
“…Passengers choose rail and bus in accordance with distance, price/value for money, time, and accessibility as key factors (Gatwick Airport, 2016). Gorecka (2016) confirmed that cost and time are major factors. Gatwick Airport (2016) only provides an overview of results so it is not clear as to the representativeness of the data.…”
Section: : Factors Affecting Airport Modal Choicementioning
confidence: 74%
“…Their findings show that public policy decisions can have a direct impact on airport choice for both airlines and passengers. Regarding accessibility, Górecka [16] highlighted that it is a critical factor that can determine passengers' airport choice. Pulugurtha [17] investigated how changes in transportation infrastructure have affected the travel time reliability of the surrounding road network in the vicinity of the airport over time and explored selected unconventional intersection designs and proposed new ingress/egress access routes from major roads near the airport.…”
Section: Airport Choice Factorsmentioning
confidence: 99%